Efektivitas Kejaksaan dalam Penanganan Kasus Korupsi Timah: Suatu Analisis Yuridis Kuantitatif - Zulkifli, Suhaila; Br. Situmorang, Zefanya Rianju; Vitri, Indah Sya; Hidayat, Afrah; Felix, Felix; Sembiring, Adrian (Verdict: Journal of Law Science, 2025)
The analysis focuses on three key dimensions: the institutional authority of the Prosecutor’s Office in conducting investigations, prosecutions, and asset recovery; the juridical and statistical indicators that reflect the institution’s performance; and the legal factors that support or hinder the Prosecutor’s Office in managing complex corruption cases in the natural resources sector. The findings reveal that the centralized and integrated structure of the Prosecutor’s Office provides a strong legal foundation for exercising investigative and prosecutorial powers in corruption cases. Quantitatively, the increase in the number of investigations, the identification of key actors, and measurable progress in state-loss recovery signify an improving level of institutional effectiveness. However, several challenges persist, including regulatory gaps in calculating state losses in extractive industries, the complexity of criminal networks, and evidentiary barriers related to proving unlawful conduct and state financial loss. In the area of asset recovery, the Prosecutor’s Office demonstrates substantial legal authority, yet limitations in cross-jurisdictional asset tracing and administrative land verification remain obstacles. The study concludes that regulatory reform, enhanced institutional capacity, and strengthened data and forensic technology support are essential to improve the Prosecutor’s Office’s effectiveness in resolving the tin corruption case and maximizing state recovery.